PENGARUH PENGENDALIAN INTERNAL TERHADAP PENGELOLAAN DAN PENDISTRIBUSIAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL KOTA DAN KABUPATEN SUKABUMI - Jeni Rahman (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The aim of this study determines the influence of internal controls for the management and distribution of zakat. The variables used in research are internal control, management and distribution of zakat. Respondents in this study were employees of the National Zakat Agency (BAZNAS) City and Sukabumi. Of the 30 questionnaires distributed, obtained 30 questionnaires which can be used in data processing. Data analysis using IBM SPSS program version 23. The statistical method used is simple linear regression test and test hypotheses using partial test (t test) and the coefficient of determination (R2). After analysis found that partial internal controls affect the zakat management, internal control influential againts zakat distribution, management and distribution of zakat together - equally influenced by internal controls. Deterninasi coefficient indicates the effect of internal controls for the management of zakat amounting to 47.5% while the remaining 52.5% is influenced by other factors not examined. While the influence of internal control over the distribution of zakat amounting to 33.8% while the remaining 66.2% is influenced by other factors not examined.